(untitled) (TAJ: Journal of Teachers Association, 2022)
Bronchiolitis is a viral infection of lower respiratory tract that occurs most commonly in young children (< 2years). It is one of the most common cause of hospitalization of infants. It has a major public health hazard throughout the world exerting significant morbidity and mortality. Methods: This randomized controlled trial study was conducted in the Department of pediatrics, Rajshahi Medical College Hospital. Total 120 patients with acute bronchiolitis were selected who were less than two years of age. Two groups were randomly selected by lottery method. One group was given salbutamol along with prednisolone (Experimental group) another was only salbutamol (Placebo group) to compare the efficacy and evaluate the outcome of both treatment groups. Result: The mean age of the experimental group was7.09±4.71 months and mean age of placebo group was 5.70±4.26 months. The majority number of patients 96(80%) came from middle class family with 30(25%) houses with crowded conditions. About 16(13.3%) patients were born in preterm condition and 18(15%) were low birth weight. Among the family members 21(17.5%) had asthma and 43(35.18%) had smoking history. After treatment notable outcome clinically observed after 3 days of treatment in experimental than placebo group (p-value <0.05). Oral prednisolone reduces 1-2 days of hospital stay (p- value <0.001) compared to placebo group. The use of prednisolone reduces the severity of disease more rapidly in association with placebo group (p - value <0.001). Conclusions: Bronchiolitis is one of the most common disease in the young children and is the frequent reason for hospitalization. Prednisolone is useful in the reducing hospital stay and improving respiratory symptoms. TAJ 2021; 34: No-2: 95-101